Counselling psychology in New Zealand. Issue 2 (2nd April 2016) - du Preez, Elizabeth; Feather, Jacqueline; Farrell, Bill
Abstract : This article offers a brief overview of the history of counselling psychology in New Zealand. It describes current postgraduate study options and registration pathways as well as the institutions and organisations that provide legislative and professional membership and support to counselling psychologists in New Zealand. Data collected from a national survey in 2014 provide insight into the demographics of the profession in New Zealand, the theoretical frameworks that are utilised and employment opportunities that exist for counselling psychologists. The article also highlights the uniqueness of a cultural and contextual approach that aligns itself with New Zealand's founding document, the Treaty of Waitangi/ te Tiriti o Waitangi which is based on the principles of partnership, participation and protection. It concludes with the challenges the profession face as a new scope of practice. These challenges include establishing a professional identity in the mental health delivery system in New Zealand and responding to an ever increasing multicultural society.